Plan estratégico para el fortalecimiento de la gestión del complejo turístico “La Rueda” de la ciudad de Guaranda, provincia Bolívar, periodo 2024-2028. - Manuel Jesús, Chicaiza Roque (2024)
One of the main objectives is to improve the capabilities of a company, uniting values, and creating a strategic plan that will serve as a guide for the proper functioning of the company. It is important to develop activities and improve processes. Apart from that, it is necessary to analyze what kind of strategy is best to achieve the objectives set by the company, both in the short, medium and long term. Business management is something very important in a company, if it is well managed the company will develop, on the contrary if it is badly managed the company will fail. A good and adequate management not only focuses on the company and what happens within it but also tries to find problems that affect productivity. Therefore, for the La Rueda Tourist Complex located in the city of Guaranda, it must be fundamental to have a vision of its future and determine its goals and objectives, identify resources, opportunities and threats. In addition, thanks to the implementation of a strategic plan, which is essential for the complex, it was possible to propose new ideas for the administrative positioning, mission, vision, organizational philosophy and programs that are essential to achieve the objectives set.